Effect of atmospheric cold plasma treatment on ready-to-eat wine-pickled Bullacta exarata. (February 2020) - Lin, Hui-Min; Zhang, Shan; Zheng, Rui-Sheng; Miao, Jia-Yu; Deng, Shang-Gui
Abstract: Ready-to-eat wine-pickled Bullacta exarata was treated by atmospheric cold plasma (ACP) at 40, 50 and 60 kV for 3 min and stored at 4 °C for 0, 3, 6, 9 and 12d. The changes of moisture, total fat, total protein content, total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), microbial quality and amino acid composition in ACP treated and untreated wine-pickled B. exarata were investigated. Results showed that total protein content, pH, TVB-N and TBARS had no significant difference among groups including ACP treatment (40 kV、50 kV、60 kV) and control group, while moisture, total fat and microbial quality had significant difference, especially in 60 kV ACP treatment group. pH, TVB-N, TBARS and total viable count significantly increased over the refrigerating storage (3, 6, 9 and 12 d), although samples treated with ACP showed lower increases, especially for the highest voltage (60 kV). Serine, glutamine, aspartic acid, glycine, threonine, leucine content increased significantly while histidine and tyrosine decreased in ACP treatment group. It was concluded that ACP could prolong the shelf life of ready-to-eat wine-pickled B. exarata with weak influence on basic composition. Highlights: 60 kV ACP treatment showed lower increases in pH, TVB-N, TBARS and TVC than CG. ACP increase glutamine while decrease histidine and tyrosine. ACP could prolong the shelf life of ready-to-eat wine-pickled B. exarata.